A word corpus of contemporary written Danish - Bergenholitz, Henning (Folia Scandinavica Posnaniensia, 2007)
The paper deals with the main problems of word corpus studies. It includes a general survey of Danish word corpora compiled so far as well as it informs of the present stage of word corpus studies in Denmark.